Comparison of Serum Procalcitonin Levels in Patients with Gram-Negative and Gram-Positive Sepsis - Bukhari, Basma; Naeem, Uzma; Bibi, Afshan; Usman, Javaid; Mustafa, Dr. Qurat ul ain; Bashir, Saima (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare rise of serum Procalcitonin levels in patients with culture-proven Gram-negative and Gram-positive sepsis.Study Design: Cross-sectional studyPlace and Duration of Study: Department of Chemical Pathology in collaboration with the Department of Microbiology, Army Medical College at Pak Emirates Military Hospital, Rawalpindi, Pakistan, from Nov 2022 to Nov 2023.Methodology: Five hundred and twenty-four blood samples were analyzed. Blood culture samples were analyzed on the fully automated Biomerieux Bact /Alert 3D system. Bacterial growth was confirmed after incubation at 35°C±2°C ambient air as per Clinical Laboratory Standards Institute guidelines. All samples which showed no growth were discarded after five days.For Procalcitonin analysis, 3ml of peripheral venous blood was collected in a serum plain tube. The serum was separated within 1 hour after collection by centrifugation at 4000rpm. Procalcitonin levels were then measured by Electro-Chemiluminescence immunoassay on the Roche COBAS 6000 chemistry analyzer as per reagent kit literature.Three hundred and seventy-two samples showed growth on blood culture and were included.Results: Out of 372 blood cultures, 195(52.4%) were positive for Gram-negative and 177(47.6%) for Gram-positive isolates. The median serum Procalcitonin levels in Gram-negative group were significantly higher than Gram-positive group (p-value